Trends of Public Relations Students in Saudi Universities towards the Use of Artificial Intelligence Technologies (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the trends of public relations students in Saudi universities towards the use of artificial intelligence technology, and to know the most prominent obstacles they face in using these technologies in academic courses and to identify their suggestions for developing academic courses to keep pace with artificial intelligence technologies. The study belongs to descriptive studies, and relies on the survey method, and the questionnaire tool was used as a tool for collecting data, by applying it to a sample of public relations students in public relations departments in media colleges in the Kingdom of Saudi Arabia, which amounted to (94) individuals. The study reached a set of results, the most prominent of which are: Drone technology came at the forefront of artificial intelligence technologies known to the respondents from public relations students at Saudi universities, and in second place came the technology of interactive chatbots, then the technology of 3D printing in third place, followed by the Google Assistant application in fourth place. The respondents believe that artificial intelligence technologies and tools in public relations are (very important), in first place with a percentage of (44.7%). The field of (providing individuals with new information) came at the forefront of the fields of employing artificial intelligence tools in public relations from the point of view of public relations students at Saudi universities, the study sample, and in second place came the field of (providing a distinctive and unique experience to customers), then the field of (developing technological skills and competencies among public relations practitioners and leaders) in third place. The majority of the respondents believe that (adding a part for practical training on the use and handling of technologies) comes at the forefront of the respondents’ suggestions for developing the curricula, and in second place came the suggestion (including more aspects about artificial intelligence and its technologies), followed by the suggestion (linking the applied aspects of public relations and the uses of artificial intelligence) in third place.
Keywords: Trends; Students; Public Relations; Saudi Universities; Artificial Intelligence Technologies